Investment and Liability on Oil Palm Land Use and Environmental Sustainability - SINAULAN, Ramlani Lina; HAMDI, HAMDI; RAHMAT, Abdul (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
Indonesia as developed country which posses’ abundant natural resources has potential as producer of oil palm plantation due to its climate and the support from oil palm plantation investors. Oil palm plantation development has to guarantee the sustainability of surrounding environmental condition based on article The Law Number 39 of Year 2014 Concerning Plantation the Law Number 31 of Year 2009 Concerning Protection and Management of Environment. Infringement against the law - such as logging the forest irresponsibly by employing land combustion method in order to create a new oil palm plantation without spending too much cost and in order to accelerate the oil palm growth process - continuously happens. Such fact has been found out through court verdicts as well as academic researches. As the result, it created deteriorated ecosystem as shown by lack of soil nutrient, land infertility, erosion and flood. Due to massive impact resulted from such action; crime against environment might be categorized as extra ordinary crime. Therefore, crime against environment requires special concern from Indonesian Financial Services Authority by imposing financial control on the Plantation Company, profile assessment and supervision from central government as well as local government.